Making civil rights law : Thurgood Marshall and the Supreme Court, 1936-1961 - Tushnet, Mark V., 1945- (New York : Oxford University Press, 1994)
From the 1930s to the early 1960s civil rights law was made primarily through constitutional litigation. Before Rosa Parks could ignite a Montgomery Bus Boycott, the Supreme Court had to strike down the Alabama law which made segregated bus service required by law; before Martin Luther King could march on Selma to register voters, the Supreme Court had to find unconstitutional the Southern Democratic Party's exclusion of African-Americans; and before the March on Washington and the Civil Rights Act of 1964, the Supreme Court had to strike down the laws allowing for the segregation of public graduate schools, colleges, high schools, and grade schools.
Making Civil Rights Law is an insightful and provocative narrative history of the legal struggle, led by Thurgood Marshall and the NAACP Legal Defense Fund, which preceded the intense political battles for civil rights. Drawing on personal interviews with Thurgood Marshall and other NAACP lawyers, as well as new information about the private deliberations of the Supreme Court, Tushnet tells the dramatic story of how the NAACP Legal Defense Fund led the Court to use the Constitution as an instrument of liberty and justice for all African-Americans. He also offers new insights into how the justices argued among themselves about the historic changes they were to make in American society.
Making Civil Rights Law provides a compelling portrait of the forces involved in civil rights litigation, bringing clarity to the legal reasoning that animated this "Constitutional revolution," and showing how the slow development of doctrine and precedent reflected the overall legal strategy of Thurgood Marshall and the NAACP. It is an important and informative work for lawyers, and students and scholars of American legal history and the history of the civil rights movement in the United States.
Includes bibliographical references (p. 317-380) and index.
Keywords: Marshall, Thurgood, -- 1908-1993.; Civil rights -- United States -- History; Judges -- United States -- Biography